ANALISIS DAN RANCANGAN PROTOTIPE MANAJEMEN DOKUMENTASI REKAYASA PERANGKAT LUNAK - Hanson Prihantoro Putro (Institut Teknologi Dirgantara Adisutjipto, 2014)
In our department, lectures found that students are difficult to create documentation, especially software documentation. Besides, software documentation is an important handbook in a software engineering. We need tools to help students or people that learn software engineering to create software documentation. This paper explains how to analyze and design a prototype for software documentation management. We propose three steps to do: problem analysis, prototype development and evaluation. First, we do the problem analysis by defining the component inputs, documentation management models and printing process. Then, the prototype is developed with object oriented software analysis and design. Finally, we create a traceability table and conduct a design testing in the evaluation step. At the result, we build analysis and design for a prototype to manage software engineering documentation with six use cases. The evaluation is conducted which well modeling the functional requirements. 26 errors are found and already refined in the documentation report. We ensure that this design is ready to implement.